An Attempted Correlation Between the Fecal Microbial Community of Chinese Forest Musk Deer (Moschus berezovskii) and Differences in Musk Production and Quality - Tingting Zheng; Qian Liu; Chengli Zheng; Xiuxiang Meng; Xue Bai; Diyan Li; Tao Wang; Jun Guo; Zhongxian Xu; Hang Jie (Animals)
Musk, a dried secretion from the sac gland near the urethral foramen of adult male forest musk deer (Moschus berezovskii), has significant economic value and is extensively utilized as a valuable component in traditional Chinese medicine. In the practice of forest musk deer breeding, musk with different colors and varying moisture contents is observed during the season when the musk reaches maturity. For many years, researchers have focused mainly on musk composition and symbiotic bacteria. However, the influence of fecal fungi on the production and quality of musk is unknown. In this study, internal transcribed spacer (ITS) analysis was employed to explore the relationships between the fungal composition of musk deer fecal and the quality and production of musk produced by each individual. The results indicate that fungal genera known to cause diseases, such as Colletotrichum and Apiotrichum, are prevalent in the feces of musk deer that produce abnormal musk. Furthermore, the fecal microbiota health index (GMHI) is lower and the intestinal microbiota dysbiosis index (MDI) is greater in musk deer producing white musk than in normal individuals. Additionally, by correlating musk production with fecal fungi, we also found that Dolichousnea and Scolecoleotia were significantly positively correlated with musk production. Moreover, Metschnikowia, Ganodermataceae_gen_Incertae_sedis, Hypoxylon, Neovaginatispora, Didymella, Dothidea, and Trichoderma were negatively correlated with musk production. This study is the first to investigate gut fungi in relation to musk production/quality, establish gut health and fungal dysbiosis links, and identify candidate fungi tightly associated with musk traits. This exploratory approach is critical for exploring uncharted territories like gut fungi in musk deer and musk traits.